Pengaruh Pertumbuhan Penduduk dan Investasi Sektor Industri serta Pengeluaran Pemerintah terhadap Produk Domestik Regional Bruto dan Pendapatan Asli Daerah Kota Bontang - Haidir Aulia Rachman; Theresia Militina; Siti Amalia (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The purpose of this study was to analyze the Influence Effect of Population Growth and Investment industry sectors as well as government spending to Gross Domestic Product and Local Revenue Bontang. The analytical tool used in this research is Multiple Regression Analysis with Path Analysis Method (Path Analysis) and by using SPSS version 22.   Results of the analysis showed that the population growth has no significant effect on the Gross Domestic Product with a significance level of 0.198 α = 0.10 Investment Industry sector had no significant effect on the Gross Domestic Product with a significance level of 0.806 α = 0.10, government spending has a significant impact on the Gross Domestic Product with a significance level of 0.011α = 0.10, Population growth not significant effect on regional revenue with a significance level of 0.738α = 0.10, Investment Industry sector had no significant effect on regional revenue with a significance level of 0.133α = 0.10, significantly influence the Government Expenditure Revenue area with a significance level of 0.095α = 0.10 and Gross Domestic Product had no significant effect on regional revenue with a significance level of 0.428α = 0.10.Keywords: Population Growth Investment Industry sector